Students’ Perception of Social Media Effect in Public Speaking Skills - Salwah Musti Ramadhani; Buhari Buhari; Nadirah Nadirah; Sam Hermansyah (Universitas Muhammadiyah Enrekang, 2024)
This research uses descriptive qualitative method as the research methodology. This research was conducted to find out students' perceptions of the impact of using social media in public speaking skills.The population in this study were students of Universitas Muhammadiyah Sidenreng Rappang in this research were 38 students’ the 3rd semester. The data collection method used in this research is interview.The results showed that the perception of students based on their experience is that social media is very impactful to improve their speaking skills and the most frequently used social media is Youtube. Social media can influence students to improve their speaking skills because in social media there is a lot of content that can be used to learn English, especially to improve students' public speaking skills such as videos, video shorts, and others.